Doktrynalna legitymizacja idei wolności słowa - Machaj, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Freedom of speech is one of the foundational values of contemporary liberal and democratic systems. The article analyzes four most important doctrinal justifications for extending afar-reaching protection for expression. First, respect for free speech is alogical corollary and consequence of respecting individual dignity and liberty. Second, free market of ideas is the best way of attaining truth and fostering healthy public debate. Third, freedom of speech is an indispensable condition of democratic political system. Fourth, respecting free speech helps create tolerant and open-minded society.
Keywords: wolność słowa; poszanowanie godności; prawda; zdrowa debata publiczna; demokartyczny system polityczny; tolerancyjne i otwarte społeczeństwo